1997
DOI: 10.1021/np970196p
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Flavonoids from Trixis vauthieri

Abstract: The crude extract of Trixis vauthieri (Asteraceae) was active against the trypomastigote forms of Trypanosoma cruzi, the protozoan that causes Chagas' disease. Bioassay-guided fractionation of this extract afforded the trypanocidal flavonoids 5,4'-dihydroxy-7-methoxyflavanone (1) and 5,4'-dihydroxy-3,6,7-trimethoxyflavone (2) besides the inactive flavonoids 3,5,4'-trihydroxy-7-methoxyflavanone (3) and 5,4'-dihydroxy-3,6,7,8-tetramethoxy flavone (4). The trypanocidal activity of 1 and 2 and the presence of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 22 publications
1
35
0
2
Order By: Relevance
“…There is a vast literature describing that natural products produced by plants, fungi and other organisms are the direct source of or inspiration for many of the currently available medicines (Newman & Cragg 2007). In this regard, our group screens the Brazilian biodiversity for new bioactive natural products using in vitro bioassays related to neglected diseases, especially Chagas disease and leishmaniasis (Ribeiro et al 1997, Rosa et al 2005. We evaluated more than 3,000 extracts from plant and fungi using an inhibition assay with trypanothione reductase (TR) (unpublished results).…”
mentioning
confidence: 99%
“…There is a vast literature describing that natural products produced by plants, fungi and other organisms are the direct source of or inspiration for many of the currently available medicines (Newman & Cragg 2007). In this regard, our group screens the Brazilian biodiversity for new bioactive natural products using in vitro bioassays related to neglected diseases, especially Chagas disease and leishmaniasis (Ribeiro et al 1997, Rosa et al 2005. We evaluated more than 3,000 extracts from plant and fungi using an inhibition assay with trypanothione reductase (TR) (unpublished results).…”
mentioning
confidence: 99%
“…They showed that these flavonoids, isolated from an active fraction of Conchocarpus heterophyllus (Rutaceae), presented low activity against trypomastigote forms of T. cruzi (IC 50 = 2116 and 787 µg/mL or 9531 and 1084 µmol/L, respectively) when compared with other flavonoids (Ribeiro et al, 1997;Ambrozin et al, 2004). Probably, the relevant activity obtained from the extract CFBH can be related to other characteristic metabolites of C. fruticosa.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ribeiro et al (1997), sakuranetin (5) isolated from leaves of Trixis vauthieri L. killed 100% of trypomastigote forms of T. cruzi Y strain in vitro, at 100 µg mL -1 . In another report, this flavanone isolated from Baccharis retusa showed in vitro activity against T. cruzi trypomastigotes (IC 50 20.2 µg mL -1 ) (Grecco et al 2012).…”
Section: Discussionmentioning
confidence: 99%